2017
DOI: 10.1186/s12955-017-0638-4
|View full text |Cite
|
Sign up to set email alerts
|

The Patient Assessment of Chronic Illness Care produces measurements along a single dimension: results from a Mokken analysis

Abstract: BackgroundAs the worldwide prevalence of chronic illness increases so too does the demand for novel treatments to improve chronic illness care. Quantifying improvement in chronic illness care from the patient perspective relies on the use of validated patient-reported outcome measures. In this analysis we examine the psychometric and scaling properties of the Patient Assessment of Chronic Illness Care (PACIC) questionnaire for use in the United Kingdom by applying scale data to the non-parametric Mokken double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…The absence of significant association between PACIC and potential determinants is common in the literature and puts into perspective the notion that it is the best instrument to assess patient experience, particularly in the context of primary interdisciplinary care. The PACIC was developed for individuals with chronic illness to measure specific actions or qualities of care congruent with the CCM,52 and most recent analyses of PACIC supported the use of the overall summary score 50,54–56,86,87. However, the fact that we did not find strong associations with hypothesized predictors raises potential questions regarding the five-dimension structure of the PACIC.…”
Section: Discussionmentioning
confidence: 72%
“…The absence of significant association between PACIC and potential determinants is common in the literature and puts into perspective the notion that it is the best instrument to assess patient experience, particularly in the context of primary interdisciplinary care. The PACIC was developed for individuals with chronic illness to measure specific actions or qualities of care congruent with the CCM,52 and most recent analyses of PACIC supported the use of the overall summary score 50,54–56,86,87. However, the fact that we did not find strong associations with hypothesized predictors raises potential questions regarding the five-dimension structure of the PACIC.…”
Section: Discussionmentioning
confidence: 72%
“…[15] The combination of the two methodologies has been shown to be useful in previous research conducted by members of our group and others. [1619] Where scale data did not conform to the assumptions of either the Mokken or the partial credit model, an iterative process of item reduction was undertaken to remove the violating items from the analysis. [20] The iterative process involved assessments of scalability, model and item fit to the PCM, category threshold disordering, local dependency, and differential item functioning (DIF).…”
Section: Methodsmentioning
confidence: 99%
“…Chronic illness is continuing to increase worldwide along with the demand to improve the care of those diagnosed with a chronic illness (Gibbons et al, 2017). Examples of chronic illness include but are not limited to arthritis, diabetes, cancer, and coronary heart disease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Examples of chronic illness include but are not limited to arthritis, diabetes, cancer, and coronary heart disease. Treating and caring for individuals with chronic illnesses has become a healthcare priority as the increasing prevalence adds stress to not only the patient but also the healthcare system (Gibbons et al, 2017). Researchers have suggested that individuals with chronic illness face uncertainty including significant disruption to family life, well-being, and quality of life as they experience unpredictable and incurable conditions (Hurt et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%